Small states beyond survival : strategies for sustenance - Nur Diyanah Mohd Azmi (2019)
The discourse on small states is largely centered on the idea of survival because the international system is perceived as anarchic and the geographical size of the state suggests a lack of human and material resources, which is symptomatic of its inherent weaknesses. Survival in this instance is referred to as a state’s ability to continue to exist and secure its national interests as much as their limited military resources allows it to. The implication of survival here only provides two outcomes for the small states: survive or perish which provides credence to the idea that small states have no place in the international system. This is a neorealist position that has lost much of its relevance today.